A duplex-specific nuclease (DSN) and catalytic hairpin assembly (CHA)-mediated dual amplification method for miR-146b detection. Issue 3 (23rd December 2022) - Han, Yu; Hu, Haihong; Yu, Lushan; Zeng, Su; Min, Jun Zhe; Cai, Sheng
Abstract : A duplex-specific nuclease (DSN) and catalytic hairpin assembly (CHA)-mediated dual amplification method has been developed. This strategy achieved a sensitive limit of detection and excellent selectivity for miR-146b detection. Abstract : A novel method for detecting miRNA has been developed using a combination of duplex-specific nuclease signal amplification (DSNSA) and a catalytic hairpin assembly (CHA). In this work, a biotinylated trigger release (BTR) probe with a biotin group at the 3′-end and a CHA reaction sequence trigger as an initiator (catalyst I) at the 5′-end was designed to hybridize target miRNA. The DSN enzyme was introduced to initiate the DSNSA. The miRNA was released to consume more BTR probes and amplify the signals. Subsequently, streptavidin-coated magnetic beads (SA-MBs) were added to the DSNSA reaction solution to remove excess BTR probes that did not hybridize with miRNA, which would then separate BTR probes and catalyst-I, to ensure detection with high selectivity and sensitivity. The catalyst-I remaining in the solution could trigger the CHA reaction to enable signal amplification in the second step. The developed method exhibits a sensitive detection limit and excellent selectivity in identifying a high sequence homology among family members.